2020
DOI: 10.1088/1757-899x/997/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

A hands-on approach to demonstrating active noise cancelling

Abstract: As noise pollution has become an increasingly major factor in the quality of urban life, noise cancelling methods started to be a relevant option for everyday life. Starting from the first active noise cancelling headphones build for aircraft industry in order to facilitate communication between pilots, in the last decade, active noise cancelling products have become more and more relevant. Factories, military and lately, civil usage of active noise cancelling technology transformed this industry and made it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Errors in making decisions by the processing system generally occur because the noise signal damages the main signal to be processed. The consequence of mixing the main signal with the noise signal is that an unexpected response is generated by the system and this will lead to other undesirable consequences, such as damage to the resulting product [1] [2]. Based on the provisions in [1][2], it can be concluded that the ability of the entire system to be able to process information correctly and be able to overcome interference from noise is the main requirement to obtain the good performance of the system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Errors in making decisions by the processing system generally occur because the noise signal damages the main signal to be processed. The consequence of mixing the main signal with the noise signal is that an unexpected response is generated by the system and this will lead to other undesirable consequences, such as damage to the resulting product [1] [2]. Based on the provisions in [1][2], it can be concluded that the ability of the entire system to be able to process information correctly and be able to overcome interference from noise is the main requirement to obtain the good performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In the development of signal processing systems, both analog processing systems and digital processing systems, testing the performance of the system against noise is carried out by testing the response of the system to the composite input signal, namely the input signal that has been mixed with the noise signal [1] [2] . The noise signal is attempted to be as similar as possible to the noise signal that appears in actual environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation